ANALISIS PEMELIHARAAN MESIN PRODUKSI PADA PT. HAYCARB PALU MITRA - Putra, Nandhika Dwi (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine and analyze the maintenance of production machinery conducted PT. Haycarb Palu Partners and find out whether the policies carried out are efficient. To achieve these objectives, using statistical and mathematical quantitative methods as a tool to help decide the maintenance policy to be taken at a certain time period. The results showed that, using preventive maintenance policy on bucket elevators and rotary screnes, the lowest preventive maintenance cost (minimum) for the bucket elevators machine occurred in the 10th month of Rp.2.994. 200, -, and for the rotary screnes machine the lowest preventive maintenance cost (minimum) at month 9 is Rp.1.398.080.-. Measurement of technical efficiency, maintenance cost policy for bucket elevators machine at month six that is equal to Rp.3.675.500, -, and for maintenance cost during the year is Rp.7.351.000, -. As for rotary screnes machine maintenance cost in the sixth month that is Rp.1.589.387 and for maintenance cost for a year of Rp.3.178.774, -, then PT. Haycarb Palu Partners can implement preventive maintenance that can save costs.